The Kind of Speech Styles in Allan Plenderleith’s “The Bunker (2017)” Movie - Sukardi Weda; Andi Elsa Fadhilah Sakti (Hasanuddin University, 2020)
This research aimed to find out the kind of speech styles in “The Bunker (2017)” directed by Allan Plenderleith. This research used descriptive method according to Martin Joos’ theory. The data were taken from The Bunker (2017) movie. The data were analyzed by watching the movie as much as possible and trying to understand all of the conversations occur in the movie. All the subtitles in the movie will be transcribed, so that they become movie scripts. Then, the writers categorized several dialogues in the movie that showed the kind of speech styles in The Bunker (2017) and the kind of speech styles appears between the two main characters, John and Margaret. The results of the research showed that the kind of speech styles in The Bunker (2017) among others is: an intimate style, a casual or an informal style, a consultative style, and a formal style. An intimate style is the style that always used between the main characters, because they are a mother and her son.